Partners for Preservation: Advancing Digital Preservation through Cross-Community Collaboration - Kramer-Smyth, Jeanne (Facet Publishing, 2018)
Who could be partners to archivists working in digital preservation? This book features chapters from international contributors from diverse backgrounds and professions discussing their challenges with and victories over digital problems that share common issues with those facing digital preservationists The only certainty about technology is that it will change. The speed of that change, and the ever increasing diversity of digital formats, tools, and platforms, will present stark challenges to the long-term preservation of digital records. Archivists are frequently challenged by the technical expertise, subject matter knowledge, time, and resource requirements needed to solve the broad set of challenges sure to be faced by the archival profession. Partners for Preservation advocates the need for archivists to recruit partners and learn lessons from across diverse professions to work more effectively within the digital landscape. Includes discussion of: the internet of things digital architecture research data and collaboration open source programming privacy, memory and transparency inheritance of digital media. This book will be useful reading for professional archivists and others responsible for digital preservation, students of archival studies and digital preservation